The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1932202x20938021
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Honors Courses: Perceptions of Engagement from the Faculty Perspective

Abstract: Research suggests that honors students are more likely to be engaged in some, but not all, aspects of the college experience, although there is less information available from the faculty perspective. This study presents findings from the Faculty Survey of Student Engagement (FSSE), comparing various engagement-related practices between faculty who teach honors courses and those who do not. Along with core FSSE items, this study uses responses from 1,487 faculty members at 15 institutions on two items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Miller and Dumford (2018) found evidence that honors students were more likely to engage in the use of learning strategies, collaborative learning, and student–faculty interaction when compared to their general education counterparts. Likewise, honors faculty was more likely to encourage collaborative learning, use of learning strategies, and student–faculty interaction (Miller et al, 2021). Students in honors programs were also found to be higher on subjective well-being compared with their non-honors peers (Plominski & Burns, 2018), and have reported that participation in honors brought about rewarding interpersonal experiences with other honors students (Mammadov et al, 2018; Perrone et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Miller and Dumford (2018) found evidence that honors students were more likely to engage in the use of learning strategies, collaborative learning, and student–faculty interaction when compared to their general education counterparts. Likewise, honors faculty was more likely to encourage collaborative learning, use of learning strategies, and student–faculty interaction (Miller et al, 2021). Students in honors programs were also found to be higher on subjective well-being compared with their non-honors peers (Plominski & Burns, 2018), and have reported that participation in honors brought about rewarding interpersonal experiences with other honors students (Mammadov et al, 2018; Perrone et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both honors programs and honors colleges provide a unique context in which to combine CBE and transdisciplinary approaches because they historically serve as an academic testing environment for innovative pedagogical practices (Sederberg, 2008; Miller et al, 2021). Honors programs, in general, typically provide connections for students to engage in enriching educational experiences (Furtwengler, 2015) in an advanced academic environment that promotes considerable rigor.…”
Section: Competency-based Educationmentioning
confidence: 99%
“…Framing service learning as a pedagogy of engagement, Stewart (2012), using pretesting and posttesting, found that honors students who participated in a service-learning program improved their sense of community connectedness, civic attitudes, and civic efficacy. More recently, research from Miller and colleagues (2021) found that faculty who teach honors courses were more likely to encourage engagement in the areas of student–faculty interaction, learning strategies, and collaborative learning, compared to their faculty peers who did not teach honors courses, yet there were no discernable differences in other areas such as higher-order learning and quantitative reasoning. Although the role of faculty is important, there is little research on faculty support for various HIPs for honors students, although research indicates that in general, effective HIPs include faculty support (Kuh, 2008).…”
Section: Faculty In Honors Colleges and Programs And Hipsmentioning
confidence: 99%